2007
DOI: 10.1161/01.hyp.0000259737.43916.42
|View full text |Cite
|
Sign up to set email alerts
|

Do Statins Reduce Blood Pressure?

Abstract: Abstract-A meta-analysis was performed of the effect of 3hydroxy3methylglutaryl-coenzyme A reductase inhibitors (statins) on blood pressure in humans including the randomized, controlled trials of statin therapy (20 trials and 828 patients) in which concomitant antihypertensive treatment (if any) remained unchanged throughout the study. A total of 291 and 272 patients were given a statin or placebo, respectively, in parallel group trials, whereas 265 took part in crossover trials receiving a statin and placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(94 citation statements)
references
References 54 publications
5
83
0
6
Order By: Relevance
“…The Iranian dietary pattern, however, was significantly associated with dyslipidemia (OR ¼ 1.73, 95%CI: 1.02-2.99). 5 Furthermore, Strazzullo et al 31 in a meta-analysis of randomized, controlled trials highlighted that statin therapy has a relatively small but clinically meaningful effect on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The Iranian dietary pattern, however, was significantly associated with dyslipidemia (OR ¼ 1.73, 95%CI: 1.02-2.99). 5 Furthermore, Strazzullo et al 31 in a meta-analysis of randomized, controlled trials highlighted that statin therapy has a relatively small but clinically meaningful effect on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 4.3 mmHg systolic and 1.6 mmHg reduction in diastolic blood pressure was unexpected. There is limited short-term trial evidence that atorvastatin treatment may reduce blood pressure in hypertensive and dyslipidaemic patients [30][31][32][33], possibly by improving endothelium-dependent vascular function [34]. A single uncontrolled trial [35] in patients with type 2 diabetes showed a 10 mmHg reduction in diastolic blood pressure, but this may partly be explained by habituation and regression to the mean.…”
Section: Discussionmentioning
confidence: 99%
“…2 This ability of statins was indeed the basis for one of the explanations that we proposed for the relatively small but clinically meaningful antihypertensive effect of these drugs in humans. 3 We share Zhou's considerations and recollect the experimental evidence in support of the concept that genetic or acquired susceptibility to the blood pressure effects of excess salt intake might partly operate through an imbalance between NO bioavailability and oxygen free radical production (see Reference 4 for review). Of course, this imbalance is not unique to hypertension (nor to salt-sensitive hypertension) in as much as it also occurs in such metabolic disorders as dyslipidemia or diabetes, which, in turn, tend to cluster with high blood pressure.…”
mentioning
confidence: 87%